1997
DOI: 10.1094/pdis.1997.81.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, Severity, and Spread of Armillaria Root Disease in Kenya Tea Plantations

Abstract: Surveys for Armillaria root disease severity were conducted over a 5-year period in small tea farms (0.5 to 1.0 ha) in the 12 tea-growing districts of Kenya. The disease occurred in all tea districts, but severity was greater in the districts east of the Rift Valley. Disease severity was associated with relative amounts of residual woody debris, especially roots, from trees and shrubs present when the land was converted to tea plantations. Excavation of tea bushes in disease centers showed that infection of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…3.1 m between plants and 4.3 m between rows. To maintain productivity in established peach orchards, it is critical to develop and adopt management practices to diminish impacts of Armillaria root disease, such as reducing inoculum sources before planting or in established orchards (Onsando et al 1997;Cox et al 2005;Prodorutti et al 2009) and development of resistant rootstock, among other measures. Previous studies have indicated that A. mellea disperses mainly by rhizomorphs in pear orchards (Rizzo et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3.1 m between plants and 4.3 m between rows. To maintain productivity in established peach orchards, it is critical to develop and adopt management practices to diminish impacts of Armillaria root disease, such as reducing inoculum sources before planting or in established orchards (Onsando et al 1997;Cox et al 2005;Prodorutti et al 2009) and development of resistant rootstock, among other measures. Previous studies have indicated that A. mellea disperses mainly by rhizomorphs in pear orchards (Rizzo et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of upper stem rot (USR) where decay occurs higher up the stem (above 1–1·5 m) and can cause palms to break in two, is much less frequent. There has been a general consensus within the industry that the primary route of infection for BSR is through roots, as is the case with other basidiomycete root‐invading pathogens, notably Heterobasidion annosum (Woodward et al ., 1998), cause of root and butt rot of conifers in temperate regions and Armillaria spp., which are pathogenic to numerous tree species (Onsando, 1997). Thus, any woody material colonized by G. boninense is a potential source of inoculum for the current stand and any colonized debris left from one stand might provide inoculum for the next planting (Hasan & Turner, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…With a 1% loss of bushes which is owed to root disease, in the 10 th years the loss of the potential crop would be 10% (Hainsworth 1952). In Kenya, the loss of tea bushes caused by root disease could reach up to 50% (Onsando et al 1997).…”
mentioning
confidence: 99%